Inovasi Model Pembelajaran Jigsaw Dalam Meningkatkan Semangat Belajar Siswa Pada Mata Pelajaran Al-Qur'an Hadist Sub Pembahasan Tajwid di MIS Islamiyah Tanjung Manis - Juhri Juhri; Juma’aroh Juma’aroh (STIKes Ibnu Sina Ajibarang, 2025)
This Classroom Action Research (CAR) aims to improve enthusiasm for learning Tajwid in the Al-Qur'an Hadith subject at MIS Islamiyah Tanjung Manis through the Jigsaw learning model. The background of this research is the low enthusiasm among students, caused by conventional teaching methods that are less interactive and monotonous. The Jigsaw model was chosen as it encourages active student participation through collaboration in small groups, where each member is responsible for learning and presenting material to their peers. The research was conducted in three cycles, following the stages of planning, implementation, observation, and reflection. Data were collected through observations, questionnaires, and interviews to measure students' enthusiasm before and after the implementation of the Jigsaw model. The results indicated a significant increase in students' enthusiasm, observed in the participation, enthusiasm, and interaction among students during the learning process. These improvements were seen from the first cycle to the second and third cycles. The findings suggest that the Jigsaw learning model is effective in boosting students’ enthusiasm for learning Tajwid. Therefore, the implementation of this model is recommended as an alternative for interactive and enjoyable learning for students at MIS Islamiyah Tanjung Manis.